Make the season bright ebook - Herring Blake, Ashley (2024)
Two exes find themselves stuck at the same house for Christmas in this holiday romance by Ashley Herring Blake, USA Today bestselling author of Iris Kelly Doesn't Date . It's been five years since Charlotte Donovan was ditched at the altar by her ex-fiancée, and she’s doing more than okay. Sure, her single mother never checks in, but she has her strings ensemble, the Rosalind Quartet, and her life in New York is a dream come true. As the holidays draw near, her ensemble mate Sloane persuades Charlotte and the rest of the quartet to spend Christmas with her family in Colorado—it is much cozier and quieter than Manhattan, and it would guarantee more practice time for the quartet’s upcoming tour. But when Charlotte arrives, she discovers that Sloane’s sister Adele also brought a friend home—and that friend is none other than her ex, Brighton. All Brighton Fairbrook wanted was to have the holliest, jolliest Christmas—and try to forget that her band kicked her out. But instead, she’s stuck pretending like she and her ex are strangers—which proves to be difficult when Sloane and Adele’s mom signs them all up for a series of Christmas dating events. Charlotte and Brighton are soon entrenched in horseback riding and cookie decorating, but Charlotte still won’t talk to her. Brighton can hardly blame her after what she did. After a few days, however, things start to slip through. Memories. Music. The way they used to play together—Brighton on guitar, Charlotte on her violin—and it all feels painfully familiar. But it’s all in the past and nothing can melt the ice in their hearts...right?